Riemann-Hilbert probleminde lineer bağımsız çözümlerin sayısı - Bazın, Abidin (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 2003)
C kompleks düzlem, y aC kapalı, sonlu uzunluklu Jordan eğrisi, D+ ve D~ sırasıyla sının y olan sınırlı ve sınırsız bölgeler, G(t) ve g(t), y üzerinde tanımlanmış Holder sınıfından olan fonksiyonlar, G{t) ^ 0, V7 e y. y üzerinde, ®+(t) = G(t).<î>{t) + g(t), V/g7 koşulunu sağlayan D+ 'da analitik 0*(z) ve D 'de analitik 0~(z) fonksiyonlarının bulunması problemine Riemann problemi denir. Tezde, kapalı veya açık düzgün eğriler için Riemann probleminin uygun sınıflardaki çözümleri incelenmiş ve çözülebilirlik koşullan belirtilmiş olup, açık eğri uç noktalarda sonsuz dönmeye sahip olduğu takdirde çözülebilirlik durumunun klasik haldekinden farklı olduğu gösterilmiştir.

The Riemann problem is considered that is formulated as follows. Suppose that we are given a rectifiable Jordan curve y cC dividing the plane of the complex variable into the interior domain D+ and the exterior domain D~, and two functions of position on the curve, G{t) and g{t), which satisfy the Holder condition, and G{t) does not vanish. It is required to find two functions: <&+{z), analytic in the domain D+, and O ~(z), analytic in the domain D~, including z = qo, which satisfy on the curve y the relation (T(0 = G(/).O-(0+g(0, Vfey. In this thesis, the solution of Riemann's problem in coresponding classes has been studied for closed and open smooth curves. The solvability conditions are defined; it is showen that when the open curve has a spiral-like form with infinite relation at the endpoint then the problem solvability is different from the classical case.
The Number of linearly independent solutions in Riemann-Hilbert problem
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Matematik; Mathematics